A new n-methoxypyridone from the co-cultivation of Hawaiian endophytic fungi Camporesia sambuci FT1061 and Epicoccum sorghinum FT1062 - Li, Chun-shun (2017)
Fil: Fil: Li, Chun-shun. University of Hawai'i at Hilo. Inouye College of Pharmacy. Department of Pharmaceutical Sciences; United States.